Industrial by-product valorization through mixed culture PHA production - Fonseca, Alexandre Miguel Alves (2018)
In the perspective of the development of sustainable industrial processes, the recovery and transformation of its by-products are mandatory. The production of polyhydroxyalkanoates (PHA) by mixed microbial cultures (MMC) is one of the possible routes to obtain. This study evaluated the possibility of using two industrial byproducts: hardwood sulfite spent liquor (HSSL) and crude glycerol (GC), as feedstock for PHA production by a MMC selected in sequencing batch reactors (SBR1 and SBR2 respectively) using the aerobic dynamic feeding (ADF) strategy. The MMC selected in SBR1, despite not being able to use the main carbon source of HSSL, lignosulphonates, revealed the capacity to consume acetate and xylose to accumulate poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBHV), and glucose biopolymer (GB). A maximum PHA content of 6.6% and a maximum production yield of 0,49 Cmmol HA/Cmmol S were obtained during the selection stage. The analysis of selected microbial community of SBR1, using fluorescence in situ hybridization (FISH) and Denaturing Gradient Gel Electrophoresis (DGGE) techniques, revealed the dominance of Alphaproteobacteria, in which Paracoccus and Rhodobacter genus were identified, but also the existence of Betaproteobacteria, Gammaproteobacteria and bacteria belonging to the classes Flavobacteria, Bacteroides Sphingobacteria. The culture selected by SBR2 despite showing the ability to consume both the glycerol and methanol fraction present in the CG, only glycerol appeared to contribute to both poly-3-hydroxybutyrate (PHB) and GB storage. Using CG, the selected MMC achieved a maximum PHB content of 37.4% and a maximum yield of 0.62 (Cmmol HA / Cmmol S) in an accumulation assay.